Utilitarianism Is Implied by Social and Individual Dominance - Johan E. Gustafsson; Dean Spears; Stéphane Zuber (Institute of Labor Economics (IZA), 2023)
The expectation of a sum of utilities is a core criterion for evaluating policies and social welfare under variable population and social risk. Our contribution is to show that a previously unrecognized combination of weak assumptions yields general versions of this criterion, both in fixed-population and in variable-population settings. We show that two dimensions of weak dominance (over risk and individuals) characterize a social welfare function with two dimensions of additive separability. So social expected utility emerges merely from social statewise dominance (given other axioms). Moreover, additive utilitarianism, in the variable- population setting, arises from a new, weak form of individual stochastic dominance with two attractive properties: It only applies to lives certain to exist (so it does not compare life against non-existence), and it avoids prominent egalitarian objections to utilitarianism by only applying if certain correlations are preserved. Our result provides a foundation for evaluating climate change, growth, and depopulation.
Keywords: D63; D81; 330; social risk; variable population; utilitarianism